2014
DOI: 10.1056/nejmoa1405707
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes 1 Year after Thrombus Aspiration for Myocardial Infarction

Abstract: T h e ne w e ngl a nd jou r na l o f m e dicine n engl j med 371;12 nejm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
244
1
7

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 337 publications
(272 citation statements)
references
References 24 publications
7
244
1
7
Order By: Relevance
“…This conclusion is confirmed by the neutral results of the TASTE (n=7244) and TOTAL (n=10 732) trials, both of which were specifically designed to reliably detect differences in clinical outcomes. 7,8 The findings of TOTAL are also consistent with the Intracoronary Abciximab and Aspiration Thrombectomy in Patients with Large Anterior Myocardial Infarction (INFUSE AMI) trial, 26 which showed no difference in infarct size with routine thrombus aspiration.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…This conclusion is confirmed by the neutral results of the TASTE (n=7244) and TOTAL (n=10 732) trials, both of which were specifically designed to reliably detect differences in clinical outcomes. 7,8 The findings of TOTAL are also consistent with the Intracoronary Abciximab and Aspiration Thrombectomy in Patients with Large Anterior Myocardial Infarction (INFUSE AMI) trial, 26 which showed no difference in infarct size with routine thrombus aspiration.…”
Section: Discussionsupporting
confidence: 59%
“…At long-term follow-up at 1 year, the TAPAS trial also showed a significant reduction in mortality that was not apparent at 30 days. 6 By contrast, the larger Thrombus Aspiration in ST-Elevation Myocardial Infarction in Scandinavia (TASTE) trial 7,8 of 7244 patients showed no significant reduction in mortality either at 30 days or at 1 year.…”
Section: Introductionmentioning
confidence: 99%
“…9 Subsequently, the recent large Thrombus Aspiration in ST-Elevation Myocardial Infarction in Scandinavia (TASTE) trial showed no reduction in mortality at 30 days or 1 year with routine thrombectomy. 10,11 Although an updated metaanalysis of thrombectomy that included the TASTE trial continued to suggest that a modest but clinically important benefit is possible, 12 the efficacy of this procedure remains uncertain.…”
mentioning
confidence: 99%
“…63 [ Coronary microvascular obstruction If the TAPAS trial 65,66 confirmed the clinical efficacy of the initial promising data about the functional or structural indexes of CMVO, 64 the TASTE trial failed to show any mortality benefit at 1 year. 67,68 Eventually, the TOTAL trial has recently clarified as, in patients with STEMI undergoing primary PCI, routine manual thrombectomy as compared to PCI alone did not reduce the risk of cardiovascular death, recurrent MI, cardiogenic shock, or New York Heart Association (NYHA) class IV heart failure within 180 days but was associated with an increased rate of stroke within 30 days. 69 The Angiojet mechanical thrombectomy device in the JETSTENT study showed an improvement in STR and a lower 1-year MACEs rate in the treatment group, compared to the direct stenting group.…”
Section: Before Catheterization Laboratorymentioning
confidence: 99%